The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.4137/ebo.s12757
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of New Functional Profiles of Protein Isoforms Yielded by Ds Exonization in Rice

Abstract: Insertion of transposable elements (TEs) into introns can lead to their activation as alternatively spliced cassette exons, an event called exonization. Exonization can enrich the complexity of transcriptomes and proteomes. Previously, we performed a genome-wide computational analysis of Ds exonization events in the monocot Oryza sativa (rice). The insertion patterns of Ds increased the number of transcripts and subsequent protein isoforms, which were determined as interior and C-terminal variants. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Exonization occurs due to the presence of splice-sites within the repetitive elements which are found overlapping with genes. There are many possible outcomes of exonization, most of which lead towards beneficial inclusion and fixation [ 96 , 97 ]. Exonization of repetitive elements and their impact on shaping the transcriptome of various species has been studied widely [ 48 , 55 , 98 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exonization occurs due to the presence of splice-sites within the repetitive elements which are found overlapping with genes. There are many possible outcomes of exonization, most of which lead towards beneficial inclusion and fixation [ 96 , 97 ]. Exonization of repetitive elements and their impact on shaping the transcriptome of various species has been studied widely [ 48 , 55 , 98 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that Ds passively enriches proteome complexity in exonization by mainly adopting the messages of the flanking introns after Ds insertion sites. 13 However, by offering acceptors that create new A-variants and DA-variants, Ds1 is more actively involved in exonization, either through its message alone or together with its flanking intron/exon, allowing the building of various new functional protein variants. We also demonstrated that, although a few of the 11 possible exonizing patterns from that Ds1 inserting into a single site are very similar to each other, even differences of only a few amino acids are enough to result in a wide spectrum of new profiles among these isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…We also performed a functional profile analysis based on the PROSITE database 12 and revealed the possibility of proteome enrichment by Ds exonization. 13 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations